Resource allocation in multiple DF relay assisted OFDM cognitive radio relay networks with the knowledge of fading statistics - Biyanwilage, Shashika; Gunawardana, Upul; Liyanapathirana, Ranjith (2013 IEEE TENCON Spring Conference, 2013)
In this paper, we study relay selection and power allocation in multiple decode-and-forward (DF) relay assisted OFDM cognitive radio (CR) relay networks. We consider the scenario where only the fading statistics between the cognitive and primary users are known at the CR transmitters. The objective of resource allocation is to maximize the instantaneous capacity of the CR network when the primary users are subject to an average interference constraint and the CR transmitters are subject to maximum transmit power constraint. The joint optimization is a mixed binary integer programming problem which is NP-hard. Thus, we propose a simple suboptimal resource allocation method.